2017
DOI: 10.1016/j.jbi.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

MetabolitePredict: A de novo human metabolomics prediction system and its applications in rheumatoid arthritis

Abstract: Human metabolomics has great potential in disease mechanism understanding, early diagnosis, and therapy. Existing metabolomics studies are often based on profiling patient biofluids and tissue samples and are difficult owing to the challenges of sample collection and data processing. Here, we report an alternative approach and developed a computation-based prediction system, MetabolitePredict, for disease metabolomics biomarker prediction. We applied MetabolitePredict to identify metabolite biomarkers and meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…The 172 classified microbial metabolites captured in HMDB are currently the best-known list of human metabolites that are originated in microbes. We previously developed data-driven computational approaches to understand how microbial metabolites are mechanistically involved in various common complex diseases using this list of 172 microbial metabolites [13][14][15][16][17][18] . Standard measures of precision (fraction of recognized entities as positive that are truly positive), recall (true positive rate) and F1 (harmonic average of the precision and recall) were calculated and compared.…”
Section: Methodsmentioning
confidence: 99%
“…The 172 classified microbial metabolites captured in HMDB are currently the best-known list of human metabolites that are originated in microbes. We previously developed data-driven computational approaches to understand how microbial metabolites are mechanistically involved in various common complex diseases using this list of 172 microbial metabolites [13][14][15][16][17][18] . Standard measures of precision (fraction of recognized entities as positive that are truly positive), recall (true positive rate) and F1 (harmonic average of the precision and recall) were calculated and compared.…”
Section: Methodsmentioning
confidence: 99%
“…The inferred de novo associations can be cross-checked against patient symptoms or other data sources that capture specific pathway-host and pathway-microbe information. Indeed, there exist a large number of human-specific and microbe-specific databases that can be explored for integration into a unified and minimally cross-compatible KBs that capture information at the DNA, RNA, transcriptome, protein, metabolic, and/or structural levels [6, 104, 105].…”
Section: Integration Of Knowledge Base and Experimental Datamentioning
confidence: 99%
“…We previously demonstrated that data-driven computational approaches have potential in uncovering mechanistic links between microbial metabolites and human diseases (colorectal cancer and Alzheimer’s disease) [24–26]. Specific for RA, we previously developed a mechanism-based prediction system, mMetabolitePredict, for human metabolome biomarker discovery and applied it to identify and prioritize metabolomic biomarkers for RA [27]. We found that among 259,170 prioritized chemicals/metabolites in human body, the subset of metabolites originated from human gut microbiota ranked highly [27].…”
Section: Introductionmentioning
confidence: 99%
“…Specific for RA, we previously developed a mechanism-based prediction system, mMetabolitePredict, for human metabolome biomarker discovery and applied it to identify and prioritize metabolomic biomarkers for RA [27]. We found that among 259,170 prioritized chemicals/metabolites in human body, the subset of metabolites originated from human gut microbiota ranked highly [27]. This finding motivated our current study (funded by Pfizer ASPIRE Rheumatology and Dermatology Research Award) to perform data-driven systematic analysis of which and how human gut microbial metabolites are involved in the immune-joint axis of the RA etiology at the genetic, functional and phenotypic levels.…”
Section: Introductionmentioning
confidence: 99%